Factors Related to The Incidence of Stunting in Adolescent at Depok Setia Negara Junior High School - Kiki Febri Ramadhan; Sintha Fransiske Simanungkalit; Widayani Wahyuningtyas (Universitas Islam Negeri Walisongo Semarang, 2019)
This research aimed to get information about factors related to the incidence of stunting in adolescent. The method used was a cross sectional study. The target population in this study were school students who attended education at the Setia Negara Junior High School. The sample consisted of students in grades VII and VIII. Determination of the sample is done by taking all students in class VII and VIII, researchers exclude students in class VII and VIII who are not willing to be respondents. The total sample of the designation was 165 people. Samples of this research were 165 respondents in Setia Negara Junior High School. This study used a statistical test Chi-Square with significance (p0,05). Of the 165 samples, consist of 26 adolescents (15,8%) stunting status, 139 adolescents (84,2%) normal status. Statistical showed that the relationship between knowledge (p=0,000), education of father (p=0,000), education of mother (p=0,000) and family size (p=0,02) with stunting. Sex and protein intake did not have a significant relationship with stunting.